Ixeris polycephala Extract Alleviates Progression of Benign Prostatic Hyperplasia via Modification of Proliferation, Apoptosis, and Inflammation - Eun-Bok Baek; Youn-Hwan Hwang; Eun-Ju Hong; Young-Suk Won; Hyo-Jung Kwun (MDPI AG, 2024)
Benign prostatic hyperplasia (BPH) is a urogenital disorder that is common in aging men. Ixeris polycephala (IP) is used in traditional medicine and contains pharmacologically active compounds. However, the effect for BPH progression has not been elucidated. We herein examined the protective potential of IP extract on a testosterone-induced model of BPH in rats. To generate the BPH model, daily subcutaneous administration of testosterone was applied for 4 weeks. During this period, the rats were also administered a daily oral gavage of IP (150 mg/kg), finasteride (positive control), or vehicle. Testosterone treatment was associated with a significantly higher prostate-to-body weight ratio, serum dihydrotestosterone (DHT) level, and prostatic gene expression of 5α-reductase compared to untreated controls. Notably, IP plus testosterone co-treatment was associated with decreased epithelial thickness, down-regulation of proliferating cell nuclear antigen (PCNA) and cyclin D1, and upregulation of pro-apoptotic signaling molecules. IP co-treatment also down-regulated pro-inflammatory cytokines, cyclooxygenase-2 (COX-2), and inducible nitric oxide synthase (iNOS) and decreased inflammatory cell infiltration compared to the levels seen in the testosterone-induced BPH. IP appears to protect rats against the progression of testosterone-induced BPH by alleviating prostate cell growth and inflammatory responses, and thus may have potential for clinical use against BPH progression.